Growth in Patients with Vesicoureteral Reflux - Nikavar, Azar (Journal of Pediatric Nephrology, 2019)
Vesicoureteral reflux (VUR) is an important cause of proteinuria, hypertension, and end-stage renal disease. Isolated VUR and its complications might impair physical growth, which are discussed in this editorial. Keywords: Growth; Vesicoureteral Reflux; Reflux Nephropathy; Child.